Knowledge Translation and Barriers to Imaging Optimization in the Emergency Department: A Research Agenda. (14th November 2015) - Probst, Marc A.; Dayan, Peter S.; Raja, Ali S.; Slovis, Benjamin H.; Yadav, Kabir; Lam, Samuel H.; Shapiro, Jason S.; Farris, Coreen; Babcock, Charlene I.; Griffey, Richard T.; Robey, Thomas E.; Fortin, Emily M.; et al.
Abstract: Researchers have attempted to optimize imaging utilization by describing which clinical variables are more predictive of acute disease and, conversely, what combination of variables can obviate the need for imaging. These results are then used to develop evidence‐based clinical pathways, clinical decision instruments, and clinical practice guidelines. Despite the validation of these results in subsequent studies, with some demonstrating improved outcomes, their actual use is often limited. This article outlines a research agenda to promote the dissemination and implementation (also known as knowledge translation) of evidence‐based interventions for emergency department (ED) imaging, i.e., clinical pathways, clinical decision instruments, and clinical practice guidelines. We convened a multidisciplinary group of stakeholders and held online and telephone discussions over a 6‐month period culminating in an in‐person meeting at the 2015 Academic Emergency Medicine consensus conference. We identified the following four overarching research questions: 1) what determinants (barriers and facilitators) influence emergency physicians' use of evidence‐based interventions when ordering imaging in the ED; 2) what implementation strategies at the institutional level can improve the use of evidence‐based interventions for ED imaging; 3) what interventions at the health care policy level can facilitate the adoption of evidence‐based interventions for ED imaging; and 4) how can health information technology, including electronic health records, clinical decision support, and health information exchanges, be used to increase awareness, use, and adherence to evidence‐based interventions for ED imaging? Advancing research that addresses these questions will provide valuable information as to how we can use evidence‐based interventions to optimize imaging utilization and ultimately improve patient care.